2008
DOI: 10.1002/anie.200800603
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength‐Dependent Photochromic Inorganic–Organic Hybrid Based on a 3D Iodoplumbate Open‐Framework Material

Abstract: Organically templated inorganic open-framework materials have been fueled by intriguing architectures and topologies as well as fascinating physical properties. [1,2] These materials can be structurally classified into two subclasses: [1,3] the zeotype materials, in which all polyhedra of the wall are exclusively tetrahedral, and the frameworks built from mixed polyhedra.However, 3D open-framework materials constructed from purely octahedral units have not been obtained so far for these materials, although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(51 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…[19] To further test our hypothesis, wavelength-dependenti rradiation experiments were carried out in the solid state. [20] Blue-violet light (420 nm) was used to irradiate Zn 2 -1 at 293 Kf or 10 min and gave rise to at wo-fold interpenetrated 3D MOF,[ Zn 2 (bdc) 2 (rctttcdp)] (denoted as Zn 2 -2 a), through as ingle-crystal-to-singlecrystal (SCSC) transformation ( Figure 3d;F igures S18 andS 19, Supporting Information). [21] This conversion,i nvolving a[ 2 + +2] photodimerization of pairs of 3-CH 3 -spy ligands, was confirmed by powder X-ray diffraction patterns and 1 Ha nd 13 CNMR spectra ( Figures S6 and S7;F igures S20a nd S21, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[19] To further test our hypothesis, wavelength-dependenti rradiation experiments were carried out in the solid state. [20] Blue-violet light (420 nm) was used to irradiate Zn 2 -1 at 293 Kf or 10 min and gave rise to at wo-fold interpenetrated 3D MOF,[ Zn 2 (bdc) 2 (rctttcdp)] (denoted as Zn 2 -2 a), through as ingle-crystal-to-singlecrystal (SCSC) transformation ( Figure 3d;F igures S18 andS 19, Supporting Information). [21] This conversion,i nvolving a[ 2 + +2] photodimerization of pairs of 3-CH 3 -spy ligands, was confirmed by powder X-ray diffraction patterns and 1 Ha nd 13 CNMR spectra ( Figures S6 and S7;F igures S20a nd S21, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…For background to hybrid materials, see: Rogow et al (2010); Thirumurugan & Rao (2008). For structures with lead halide building blocks, see: Li et al (2008); Zhang et al (2008).…”
Section: Related Literaturementioning
confidence: 99%
“…E66, m1259 Inorganic metal-halide building-blocks have received special attention with respect to the construction of inorganicorganic hybrid materials (Rogow et al, 2010;Thirumurugan et al, 2008). Among these materials octahedral building blocks of lead halides are frequently found and numerous crystal structures, from one-dimensional chains to threedimensional frameworks (Li et al, 2008;Zhang et al, 2008), were observed. Herein we report the crystal structure of the title compound, (C 5 H 7 N 2 )[PbI 3 ] (I).…”
Section: Sup-1mentioning
confidence: 99%
“…Recently reported thermochromic iodoplumbates [7e10] and iodobismuthates [11,12] as well as photochromic chlorobismuthates [13e16] and iodoplumbates [17] exhibit interesting component-structure-property relationship. Comparatively, chromism based on organicinorganic iodoargentate hybrids is rarely reported [18,19].…”
Section: Introductionmentioning
confidence: 99%